Medium chain triglycerides (MCT) formulas in paediatric and allergological practice - Łoś-Rycharska, Ewa; Kieraszewicz, Zuzanna; Czerwionka-Szaflarska, Mieczysława (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Fats constitute the most significant nutritional source of energy. Their proper use by the body conditions a number of complex mechanisms of digestion, absorption, distribution, and metabolism. These mechanisms are facilitated by fats made of medium chain fatty acids; therefore, they are an easy and quick source of energy. Thus, an increased supply of medium chain triglycerides (MCT) is particularly important in patients with disturbances of digestion and absorption such as disturbed bile secretion, classic coeliac disease, short bowel syndrome, inflammatory diseases of the intestines, disturbed outflow of lymph, some metabolic disease, and severe food allergies, as well as in prematurely born neonates. Use of preparations containing an additive of MCT is limited, especially if they are to be used for a longer period of time. With a large quantity of MCT in a diet, there is a risk of deficiency of necessary unsaturated fatty acids and some fat-soluble vitamins. The caloricity of MTC compared to long-chain triglycerides is lower, and formulas with MCT are characterised by higher osmolality. Medium chain triglycerides is not recommended as an additive to standard formulas for healthy children. The use of MCT should be limited to strictly specified medical indications.